Comparative study of student resilience: A mixed-methods approach in modern and salaf Islamic boarding schools - Gunawan, Satria Amir Makmun; Rosyidah, Amiliya Nur; Azzahra, Fatimah; Wahyuni, Esa Nur; Hady, M. Samsul; Rahayu, Iin Tri (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v10i1.3807, 2025)
Adolescents today often face psychosocial  pressures that have a direct impact on their well-being, academic achievement and social engagement. Based on data exposure, it shows that 30% of adolescents in Indonesia experience academic stress which can reduce their motivation to study and mental health. This study aims to 1) determine the level of resilience of students in modern and salaf Islamic boarding schools; 2) to determine whether there is a significant difference in the resilience of students between modern and salaf Islamic boarding schools and; 3) explore factors and strategies of pesantren that can strengthen the resilience of students in modern and salaf pesantren Islamic boarding schools. This study uses a mixed method approach with a sequential explanatory research design. The determination of the number of samples was determined based on the percentage (15%) of the population, then the researcher used a probability sampling technique  with a simple random sampling  type in determining the sample. The results of the study showed that the total average level of resilience of students in modern Islamic boarding schools and salaf was 38.71. In more detail, the average level of resilience in modern Islamic boarding schools (38.94) and salaf Islamic boarding schools (38.28) shows a high category in both Islamic boarding schools. Based on the results of the interviews, there are several factors that strengthen the resilience of students, such as 1) adaptability and emotional independence; 2) high learning motivation; 3) spiritual closeness; 4) social support; 5) the role of murobbi and counselors; 6) Islamic boarding school values and culture; 7) there are exemplary figures and; 8) Surveillance and protection system. In addition, there are also Islamic boarding school strategies that can strengthen the resilience of students, such as 1) tiered, systematic and familial assistance; 2) preventive and responsive approaches; 3) spiritual and emotional strengthening activities as mental reinforcement and 4) parental involvement and collaboration.